The Potential Utilization of Metaverse as a Praying Space from the Perspective of Maslahah Mursalah - Fikri , Mursyid; ., Supardin; Syatar, Abdul; ., Fatmawati; ., Indriana (Journal of Ecohumanism, 2024)
The Metaverse has emerged as a promising virtual platform for various purposes, including its potential use as a praying space. In this context, it is important to examine the potential utilization of the Metaverse as a praying space while considering the perspective of Maslahah Mursalah, a concept in Islamic law that prioritizes public welfare. This article aims to explore the potential utilization of the Metaverse as a praying space from the perspective of Maslahah Mursalah. By analyzing literature and the concept of Maslahah Mursalah, this article discusses the positive and negative implications of using the Metaverse as a praying space, as well as how the principle of Maslahah Mursalah can be used as an evaluation framework. The findings of this research are expected to provide deeper insights into the possibility of using the Metaverse in religious contexts, while considering the common welfare that is the primary focus in the perspective of Maslahah Mursalah.